Faserstoffprojekt Ravensbrück / Fürstenberg : vergessen Erinnern Denkmal (Berlin : Künstlerhaus Bethanien Berlin, 2004)
Almond, Darren ; Becker, Sandra ; Binder, Pat ; Boden, Roland ; Brenner, Birgit ; Camnitzer, Luis ; Dreher, Margarete ; Ersen, Esra ; Favre, Valérie ; Haaning, Jens ; Heijne, Mathilde ter ; Hertzsch, Eva ; Page, Adam ; Herz, Rudolf ; Matz, Reinhard ; Jones, Ronald ; Junghanss, Lisa ; Lerch, Karl-Hartmut ; Kleinknecht, Hermann ; Libera, Zbigniew ; Locher, Thomas ; Lopez-Menchero, Emilio ; Lukac, Jenni ; Maltzahn, Katrin von ; Metzel, Olaf ; Middendorf, Angelika ; Miller, John ; Molis, Christine ; Nicolai, Olaf ; Nisic, Natacha ; Othoniel, Jean-Michel ; Palavrakis, Apostolos ; Ramberg, Lars ; Rehberger, Tobias ; Rheinsberg, Raffael ; Rinn, Rivka ; Rosenberg, Aura ; Sanguineti, Pietro ; Schaerf, Eran ; Schefferski, Roland ; Schleyer, Susanne ; Stih, Renata & Schnock, Frieder ; Schütz, Richard ; Weiberg, Kerstin ; Schimada, Yoshiko ; Shuravlev, Anatolij ; Steinbrecher, Erik ; Thomaes, Monique ; Weinberger, Lois ; Westphalen, Olav ; Winter, Georg ; Zinganel, Michael
Duits
boek